Identifying Selected Sources of Variation in the Results of Gymnasium Examination Using ANOVA - Król, Anna (Identyfikacja wybranych źródeł zmienności w wynikach egzaminów gimnazjalnych z wykorzystaniem analizy wariancji, 2011)
One of the parts of the Polish external examination system in preliminary education is the Gymnasium Examination. It is the first examination taken by the students, having serious impact on their prospective educational path, and because of its importance, a comprehensive and extensive study of the examination results should be carried out, allowing for identification of the factors influencing students’ scores. This paper attempts to investigate the sources of variations in results of the Gymnasium Examination conducted in 2010 in Lower Silesia and Opole voivodships, in particular focusing on the extent to what the differences in students’ scores are associated with the location of the gymnasium, the sex of the student and the dyslexia diagnosis. The results could provide the basis for guidelines in creating equal opportunities policies in education.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 194, s. 88-101
Keywords: egzaminy; analiza wariancji; szkolnictwo ponadpodstawowe; exams; variance analysis; post-primary education